Cyber warfare and terrorism concepts, methodologies, tools, and applications (Critical Explorations, 2020)
"This book explores the utilization of online tools by terrorist organizations to communicate with and recruit potential extremists and examines effective countermeasures employed by law enforcement agencies to defend against such threats"--